Economics of Milk Producton In The Thrissur District - Sreejith TK (Department of Agricultural Economics, College of Horticulture, 1994)
The study entitled “Economics of milk production in the Thrissur district” was undertaken to study the economics of the milk production , to work out the income elasticities, to understand the marketing channels for milk and to work out the resource use efficiency in milk production with regard to certain explanatory variables such as labour cost, cost of oil cake, compound feed, straw and other types of feeds fed per day. The study was conducted using primary and secondary sources of data. Production, consumption and prices of milk and major inputs used in the production of milk for the state as a whole were analysed using secondary data. Engel functions were fitted to estimate income elasticities by taking expenditure on milk and milk products by the various monthly per capita expenditure groups. Primary data pertaining to socio-economic characteristics, livestock position, production and marketing aspects, feeding, labour and other expenses and details of cash farm income from milk, consumption pattern of milk and major sale outlets for milk were collected with the help of structured schedule from 120 sample households selected by multi-stage random sampling method. In addition to tabular analysis, functional relationship between milk yield and relevant variables were studied by fitting Cobb-Douglas production function for one lactational period. The study revealed that the overall milk production in Kerala was increasing over the years. The milk production of crossbred cows was also increasing but that of the non-descript cows was also increasing but that of the non-descript cows showed a fluctuating trend over the last 10 years. The Engel function fitted using the National Sample Survey (NSS) data on milk and milk products in Kerala showed that the income elasticities estimated for the function (log-linear) was lower than unity, but positive, in the 38th and the 43rd rounds of NSS for rural as well as urban households. This revealed that the expenditure incurred on these items increased less than proportionate to their incomes. The rise in prices of these commodities between the two periods might have led consumers to spend proportionately less of their income during 1987-88 compared to the amount spent during 1983 although aggregate expenditure increased from 1983 to 1987-88. The economics of milk production revealed that the major cost involved for maintaining a cow-in-milk was feed cost followed by labour cost, veterinary and miscellaneous charges. The farm returns increased with increase in output among the sample households. Though the farm returns did not cover the total cost incurred by the households, it covered the feed cost and other cash costs incurred by the producers. The study also revealed that except those households with low productive animals all others were making gross profit from dairying but the net profit was negative among almost all households. The importance of milk co-operatives and their effective and dominant role in the marketing of milk has been confirmed by this study. The production function analysis carried out showed the scope for increasing the efficient use of various resources. Hence it is recommended that in order to enhance the milk production, farmers have to use the various resources more effectively and efficiently… On account of limitation of resources the sampling design followed in this study did not include the lactation stage of the animals as one of the sampling criteria, and each sample household was contacted only once and the data often relate to the period just prior to the investigation date. So the cost of production studies should be considered only as an indicative of average pattern prevailing. The observations may also suffer from biases in the secondary data.